THE Effect of Emotional Advertising and Environment Advertising on Purchase Decision at Shopee Marketplace - Reza Gustiani Ratu; Ce Gunawan (Industrial Engineering Study Program, Pattimura University, 2020)
Advertising has an important role for influencing purchasing decision. The purpose of this study is finding the impact of Shopee Advertising toward purchasing decision at shopee marketplace. Research methode that is used is quantitative methode. Analysis technique is using Multiple Regression Analysis by using 100 respondens, The results of this study are emotional advertising has an effect significant toward purchase decision partially; environment advertising does not have an effect toward purchase decision partially; and emotional advertising and environment advertising have an effect significant toward purchase decision simultantly